2021
DOI: 10.46729/ijstm.v2i1.165
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Small Horizontal Axis Wind Turbine with Airfoil NACA 4412

Abstract: The horizontal axis wind turbine (HAWT) design with low wind speed requires blade geometry selection. The analysis uses the potential flow panel method and the integral boundary layer formulation to analyze wind flow around the airfoil. The blade design with the blade element momentum (BEM) theory has an aerodynamic coefficient value along the blade. Power wind calculates to model the wind shear pressure at each blade. This research aims to determine the wind turbine rotor based on the performance, including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The realizable torque, TR, from a wind turbine is obtained by: TR=CT(1/2) ρ A V 2 rm (5) CT = TR / (1/2) ρ A V 2 rm (6) where rm=(D/2)√[ (1 + λ 2 ) /2] (7) The power coefficient, CP is a function of wind turbine rotor characteristics and the working tip speed ratio of the turbine; it can be expressed in the following form. CP = PR / (1/2) ρ A V 3 (8) Where, PR is the realized power from a wind turbine and is obtained as PR= TR ω (9)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The realizable torque, TR, from a wind turbine is obtained by: TR=CT(1/2) ρ A V 2 rm (5) CT = TR / (1/2) ρ A V 2 rm (6) where rm=(D/2)√[ (1 + λ 2 ) /2] (7) The power coefficient, CP is a function of wind turbine rotor characteristics and the working tip speed ratio of the turbine; it can be expressed in the following form. CP = PR / (1/2) ρ A V 3 (8) Where, PR is the realized power from a wind turbine and is obtained as PR= TR ω (9)…”
Section: Methodsmentioning
confidence: 99%
“…They found that an efficient blade shape depends on the performance of the selected airfoils. Widiyanto et al [3] held an analysis for the performance of a SHAWT with airfoil NACA 4412. The analysis examined wind flow around the airfoil using the integral boundary layer formulation and the potential flow panel approach.…”
Section: Introductionmentioning
confidence: 99%
“…It should be explained that the SG6042 and SG6043 airfoils were designed by Giguere and Selig [30] for application in SWT blades. Although the NACA4412 airfoil was initially designed for aviation purposes, because of the simplicity of its manufacturing process due to its flat pressure side, in recent years, it has attracted lots of attention from researchers working on SHWT blades [31,32]. Figure 1 shows the geometry of the selected airfoils in Cartesian coordinates.…”
Section: The Selected Swt As a Case Studymentioning
confidence: 99%
“…Beberapa bulan kemudian diikuti oleh Charles F.Brush yang mengembangkan turbin otomatis untuk menghasilkan listrik [7]. Turbin angin terdiri turbin angin vertikal dan horizontal, yang juga terdiri dari turbin aliran terbuka [8] yang dianalisa menggunakan teori teori Lanchester-Betz [9][10], dengan nilai Betz = 0.593 dan turbin dengan ducted [2]. Kecepatan rata -rata angin lebih dari 5 m/s agar dapat dikembangkan turbin angin poros horisontal [11] [12].…”
Section: Pendahuluanunclassified